Socio-cultural challenges of preserving historical heritage in Africa: Lessons from the King’s palace, Akure (2009)
Historical heritage are physical monuments and landmarks that have traditional significance through a lifetime property, it cannot remain for so long without being preserved and protected to retain its cultural and metaphorical value. It is a known fact that the dynamics of change has brought about the destruction of many landmarks of progress and history, bequeathed by the past generations. Recent events had led to some structural problems that brought the King’s palace, Akure, Nigeria (the case study) to a state of deformity, to the extent of it loosing its splendor. The paper explore the rich cultural heritage of the Yorubas of the Southwestern Nigeria. The paper further review the historical antecedent and the socio-cultural factors impacting on the contemporary use of this palace-museum. The paper underscores the relevancy of the primordial historical antecedent of the towns under study and advocate approaches to harness the cultural potentials for greater positive tourism gain. Copious use of pictures, imaees and obiects are emnloved to reflect contemnorarv dimensions of the timeless vernacular architecture.